2004
DOI: 10.1111/j.1464-410x.2004.04862.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous stone surgery in the obese: outcome stratified according to body mass index

Abstract: according to the World Health Organization classification of body mass index (BMI), i.e. < 25, 25-29.9 (overweight), 30-39.9 (obese) and > 40 kg/m 2 (morbidly obese). The outcomes of surgery in these four groups were compared. RESULTSThere were no statistically significant differences in operative duration, decrease in haemoglobin concentration, postoperative analgesic use, hospital stay and stone-free rates; nor was there a higher complication rate in patients who were obese. CONCLUSIONThe outcome of PCNL is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
1
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 20 publications
2
57
1
7
Order By: Relevance
“…Urologists are now seeing more patients who are morbidly obese for the treatment of renal stones. [12] Morbid obesity is known to be associated with diabetes mellitus (DM), hypertension, respiratory diseases, and many other serious health problems. These patients tend to be at higher risk for complications related to anesthesia during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Urologists are now seeing more patients who are morbidly obese for the treatment of renal stones. [12] Morbid obesity is known to be associated with diabetes mellitus (DM), hypertension, respiratory diseases, and many other serious health problems. These patients tend to be at higher risk for complications related to anesthesia during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] El-Assmy and colleagues 7 analyzed the outcomes of PCNL in a series of 92 patients at a single high-volume centre with a BMI >40 and found no significant effect on complication rates or stone-related outcomes. There are likely to be multiple factors contributing to the inferior stone-free rate and higher re-treatment rates demonstrated by this study.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] This study was conceptualized on the basis that obese patients with a BMI in excess of 40 pose unique challenges in terms of intra-operative and postoperative care. To effectively manage such patients, urologists must be able to pre-empt the likely challenges and implement strategies to minimize risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its incidence is increasing day by day due to inappropriate dietary patterns and decreased physical activities (2). Outcomes of PNL which is frequently performed in stone surgery today are controversial for obese patients There have been some studies reporting that obesity adversely affects the results while some others showed no effect (3,4). We investigated outcomes of PNL in morbid obese patients [body mass index (BMI) ≥40 kg/m 2 ] using the data of our clinic by comparing with a control group.…”
Section: Introductionmentioning
confidence: 99%